Penilaian Higher Order Thinking Skills (HOTS) Menggunakan Quizizz Pada Materi Usaha dan Energi - Nabila Ayunda Putri; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Kappa Journal, 2021)
The aim of this research was to produce a web based instrument test to assess higher order thinking skills that are feasible and to describe the profile of students higher order thinking skills. This research using Research and Development (R&D) model from Borg and Gall with ADDIE (Analysis, Design, Development, Implementation, and Evaluation ). Data collection techniques in this study are the validation method that done by three lecturers from the physic department of State University of Surabaya and test method that done by 29 students of class X MIPA-2 SMA At-Ta’miriyyah using Quizizz. The data that has been collected were analyzed using quantitative decriptive analysis method. The percentage of average theoritical validity in the realms of construction, language, and media is is 97.03% or in the very feasible category. The result of product trials on 29 students analyzed the level of distinguishing power, reliability, and item validity. From the analysis obtained empirical validity as many as 10 questions declared empirically feasible. The appropriate test instrument is then used to describe the profile of students higher order thinking skills abilities. A viable test instrument is then used to describe the student's high-level thinking ability profile. 44.83% of students in very high categories, 13.79% with good categories, 0% with sufficient categories, and 41.38% with less categories. The ability to think high level in the competency of analyzing (C4) is lower at 67.49% compared to the evaluating competency (C5) of 80.46%.